Establishing a Lifelong Learning System by developing Higher Vocational Education: A case of China - Jie Xiong (Adult Education Research Conference, 2006)
This paper reveals that higher vocational education (HVE) is playing a key role for establishing a lifelong learning system in China. Discussions are based on the theory that higher education is at the core to build a lifelong learning system with a focus on the concept of vertical integration.
Keywords: higher vocational education; higher education; lifelong learning system; vertical integration